The soils of the USA - West, Larry Thomas, 1951-; Singer, Michael J. 1945-; Hartemink, Alfred E., 1964- (Springer, 2017)
This book provides an overview of the distribution, properties, and function of soils in the U.S., including Alaska, Hawaii, and its Caribbean territories. It discusses the history of soil surveys and pedological research in the U.S., and offers general descriptions of the country's climate, geology and geomorphology. For each Land Resource Region (LRR) - a geographic/ecological region of the country characterized by its own climate, geology, landscapes, soils, and agricultural practices - there is a chapter with details of the climate, geology, geomorphology, pre-settlement and current vegetation, and land use, as well as the distribution and properties of major soils including their genesis, classification, and management challenges. The final chapters address topics such as soils and humans, and the future challenges for soil science and soil surveys in the U.S. Maps of soil distribution, pedon descriptions, profile images, and tables of properties are included throughout the text.- Resumé vydavatel
Keywords: půdy -- Spojené státy americké; fyzická geografie -- Spojené státy americké; pedologie -- Spojené státy americké; soils -- United States; physical geography -- United States; pedology -- United States; elektronické knihy; sborníky; electronic books; sborníky konferencí